Comparison of definitions of bronchopulmonary dysplasia to reflect the long-term outcomes of extremely preterm infants - Ga Won Jeon; Minkyung Oh; Juyoung Lee; Yong Hoon Jun; Yun Sil Chang (Scientific Reports, 2022)
Abstract Survivors of neonatal bronchopulmonary dysplasia (BPD) have persistent respiratory, neurodevelopmental, and growth impairment over the first few years of life and later childhood, which represents an emerging burden for health systems. Therefore, there is an increasing need for a new definition and grading system of BPD that predicts long-term outcomes of high-risk infants who need timely and proper intervention to improve outcomes. We compared new definitions of BPD (National Institute of Child Health and Human Development [NICHD] 2018 and Neonatal Research Network [NRN] 2019) to the original NICHD 2001 definition at 3 years of age using a nationwide cohort of extreme preterm infants. New definitions and severity grading were clearly related to respiratory, neurodevelopmental, and growth impairments at 3 years of age and at 18–24 months corrected age (CA), whereas the original NICHD 2001 definition was not. Furthermore, the negative effect of BPD on growth was ameliorated at 3 years of age compared to 18–24 months CA. However, the negative effect of BPD in neonates on the respiratory system and neurodevelopment persisted at 3 years of age. These new definitions should be adopted to identify high-risk infants and improve long-term outcomes by exact diagnosis and BPD severity classification.